Cracks in the Self: A Poetry Collection Exploring Narcissism and Its Coping Mechanism in Youth - Chintya Margaretha; Liem Satya Limanta (Institute of Research and Community Outreach - Petra Christian University, 2024)
When a girl grows up with an authoritarian parent, the trauma causes her to develop narcissistic personality disorder (NPD) in her young adult years, disrupting her ability to form healthy relationships with her mother, friends, and especially herself. To escape any emotional discomfort, she turns to non-suicidal self-injury (NSSI) as a coping mechanism. This narrative poetry explores the progression of Renee's life from childhood to her struggle with NPD in young adulthood. It highlights how dangerous NPD is when Renee resorts to NSSI to deal with the negative reactions from others. This creative work underscores the seriousness of NPD since it may lead to a harmful coping mechanism called NSSI.